The Analysis of the Interpersonal and Declaratory Acts of the Humorous Utterances In Bernard Shaw's Comedy You Never Can Tell A Pragmatic Study - Salman, Sahira Musa; Noori, Baida'a Faisal (Al-Adab Journal, 2022)
.